Normalization-Simple Additive Weighting to Determination of a Single Tuition - Winda Aprianti; Herfia Rhomadhona; Jaka Permadi; Yuniska Fithriyyah (LPPM Politeknik Aceh Selatan, 2022)
Determination of a single tuition appropriately is important to ensure that every student gets a fair single tuition in accordance with their economic conditions. The single tuition team to determine a single tuition sometimes they have differences of opinion in determining a single tuition so that it requires a relatively long time. This problem can be solved by applying Simple Additive Weighting to student data. The collected data is formed into Data1 and Data 2. There is a value of 0 for the cost attribute so that it requires normalization which can solve the problem. The results of the application of Simple Additive Weighting facilitate the determination of a single tuition because by entering student data a preference value is generated as a reference for determining a single tuition. Application in Data 1 produces several similarities in preference values but is in different groups, but the application of Data 2 always results in different preference values. This difference shows that the application of Simple Additive Weighting to Data 2 is better than the application of Data 1.